A Study on Liqid- Liquid Etraction on Iron(III) With 2,5- Diphenyi Oxazole - Hussain, A. F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A study on liquid- liquid extraction of Iron (III) in Benzene has been made. The effect of different parameters such as type of medium and time of equilibration, concentration of metal ion, type of organic solvent, and effect of cations on distribution ratio of Iron (III). Has been studies the stoichiometry of the extracted species determined using slope analysis method and found to be (M:L) (1 :3).